How green is an urban tree? The impact of species selection in reducing the carbon footprint of park trees in Swedish cities - Lind, Erik; Prade, Thomas; Sjöman Deak, Johanna; Levinsson, Anna; Sjöman, Henrik (Frontiers in Sustainable Cities, 2023)
Planting trees in urban areas can mitigate some of the emissions generated in cities by carbon sequestration (annual uptake of CO2 through the process of photosynthesis) and carbon storage (amount of carbon stored in the tree’s biomass throughout its lifespan). The aim of this study was to calculate the carbon footprint from nursery production to final establishment of different tree species grown for planting in urban parks in a northern European context. The analysis included a cradle-to-gate approach and investigated the amount of carbon the adult trees needed to sequester in order to compensate for initial carbon emissions and which temporal perspectives are of concern. Greenhouse gas emissions were estimated based on an inventory of consumption of fuels, energy, materials and other production inputs during cultivation, delivery, planting and establishment of three different tree species in three different locations in Sweden. The species considered in the analysis (Salix alba, Quercus rubra, Pinus sylvestris) were selected due to significant differences in their growth rates. Salix alba is a competitive strategist in resource-rich habitats, and is proficient at converting these resources into vigorous growth. Pinus sylvestris is a pronounced stress strategist with good ability to handle resource-limited habitats, and invests in traits accordingly, resulting in significantly slower development. Quercus rubra has its main distribution in cool and moderately resource-rich habitats, but has relatively high stress tolerance and is considered intermediate between the other two species in terms of growth rate. The results showed that within 16 years of planting, all species in all cities, except Pinus sylvestris planted in Umeå, compensated for initial carbon emissions, i.e. showed net absorption of CO2 after emissions from cultivation, delivery, planting and establishment of the trees had been deducted. There was a clear link between the time by which compensation of initial carbon emissions was achieved and growth rate of the different species, with the fast-growing Salix alba showing the best results. The single largest source of emissions among all activities carried out during cultivation, delivery and planting of all species, regardless of the city in which they were planted, was fuel consumption during tree planting.